THE CORRELATION BETWEEN STUDENTS’ READING ATTITUDES AND READING FREQUENCY: THE CASE STUDY OF SECOND GRADE STUDENTS OF SMPN 26 PERUM. RINDANG GARDEN KEC. BATU AJI BATAM: THE CASE STUDY OF SECOND GRADE STUDENTS OF SMPN 26 PERUM. RINDANG GARDEN KEC. BATU AJI BATAM Alpino Susanto, susanto.alpino40@gmail.com, Universitas Putera Batam - alpino Susanto (Universitas Putera Batam, 2014)
ABSTRACTThis research explored the Junior High School Students second grade with regard to the correlation between reading attitude and reading frequency. Reading attitude composed of academic reading and recreational reading. The Elementary Reading Attitude Scale and the Frequency Questionnaire were administered to the students of SMPN 26 Batu Aji as the population of the study. The sample of the study is 37 students from 1 class of the second grade that questionnaire were taken. This study presents the correlation between reading attitude (X3) and reading frequency, as well as the correlation between academic reading (X1) and recreational reading (X2) with reading frequency (Y). The Pearson Corrrelation was used to measure the correlation by the r value. As the result, 34% of the variability in academic reading is attributable to difference in reading frequency. 28% of the variability in recreational reading is attributable to difference in reading frequency and 36% of the variability in reading attitude is attributable to difference in reading frequency.